The Influence of Context Aspects towards Input Aspects of Science Practical among Science Teachers in Rural Secondary Schools of Sabah - Crispina Gregory K Han; Lay, Yoon Fah; Getrude C. Ah Gang@Grace; Lawrence Alan Bansa; Mohamad Nizam Nazarudin ,; Colonius Atang (2018)
This study aims to explore the influence of science practical context towards the input of science practical among the science teachers in 69 rural secondary schools in Sabah. A total of 357 science teachers were selected by stratified sampling method. This study is a quantitative non-experimental study using the survey method to collect data. The instrument of science practical context aspects and science practical input aspects questionnaires were used to collect data. Statistical Package for Social Science (SPSS) version 21.0 for Windows and the software of 'Smart Partial Least Square (SmartPLS) version 3.2.7 was used to analyze the collected quantitative data. The findings show that the level of the science practical context aspects and science practical input aspects are at the stage of 'High' (3:46- 4.64) among the science teachers at rural secondary schools in Sabah. The value of composite reliability for context aspects is 0.984 and for input aspects is 0.939. The results also showed there is a significant positive correlation between the science practical context aspects and the science practical input aspects (β=0.473, p<0.05). There is a modest positive effect and significant between the science practical context aspects towards the science practical input aspects (β = 0.473, p <0.05). A total of 16% of science practical context can affect the science practical input aspects. The implications of this study showed that science teachers should examine the science practical input aspects coincides with the implementation of science practical in addition to considering the science practical process and product aspects.